SHARIA TOURISM CULTURE IN INDONESIA: SHARIA TOURISM CULTURE IN INDONESIA - Ramadani, Lalu Ahmad (Journal Of Islamic Ekonomic and Business, 2022)
The purpose of this study is to find out how sharia tourism culture exists in Indonesia, methodology using qualitative research type analysis, general findings that occur in halal tourism culture in Indonesia in general there are still many stake holders who refuse some destinations to be used as halal tourism, the conclusion of success is driven byeffectiveadvertising and marketing plans. Relationships with local travel agencies need to be improved and maintained properly as a form of cooperation with travel agencies and airlines to promote sales to reach the target market well, while providing incentives for family travel, travel marts, product knowledge training, and agency to be improved.